Thrombosis: A Laboratory Diagnosis of Cerebral Sinus Venosus Thrombosis (CSVT) with Cardiac Myxoma - Cynthia; Suzanna Immanuel (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
Cerebral sinus venous thrombosis (CSVT) is a venous thromboembolism (VTE) is very rare about 0.5%-3% of all types of stroke, often found in young patients, estimated incidence in adults 3-4‰ and children 7‰, ratio of girls to boys 3:1.3,4,5,6 The main causes of CSVT differ in developed and developing countries. In preantibiotics, the main cause of CSVT is a septic process. Currently, it is generally due to the process aseptic. According to Bushnell et al. conversion to bleeding is reported to occur in 30-35% patient. Autopsy findings show that 10% of the causes of death are from cerebrovascular disease CSVT.3,4,5 We report a case of CSVT in a 83-year-old female patient. The patient had a diagnosis of CSVT with cardiac myxoma delivered to the laboratory from emergency room installation on the 28th December 2017, 12.40 WIB for routine hematology examination, PT, APTT, D-dimer, glucose while, SGOT, SGPT, urea, creatinine, electrolytes, calcium and magnesium with clinical evidence of decreased consciousness, convulsions and weakness of the right extremity.